Twenty lectures on thermodynamics - Buchdahl, H. A. (Hans Adolph), 1919- (Pergamon Press (Australia), 1975)
Twenty Lectures on Thermodynamics is a course of lectures, parts of which the author has given various times over the last few years. The book gives the readers a bird's eye view of phenomenological and statistical thermodynamics. The book covers many areas in thermodynamics such as states and transition; adiabatic isolation; irreversibility; the first, second, third and Zeroth laws of thermodynamics; entropy and entropy law; the idea of the application of thermodynamics; pseudo-states; the quantum-static al canonical and grand canonical ensembles; and semi-classical gaseous systems. The text.